2023
DOI: 10.3390/fermentation9020153
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Lacto-Fermented Cricket (Acheta domesticus) Flour and Its Influence on the Quality Parameters and Acrylamide Formation in Wheat Biscuits

Abstract: The aim of this study was to evaluate the influence of different amounts (40, 80 and 100 g) of non-fermented and fermented (with Lactiplantibacillus plantarum No. 122 and Lacticaseibacillus casei No. 210) cricket flour (Cr) on the quality characteristics and acrylamide formation in wheat biscuits (WB). The main formula for WB preparation consisted of 280 g of wheat flour, 100 g of margarine, 50 g of saccharose, 3 g of vanilla sugar, 50 g of eggs, 1.5 g of salt and 2.0 g of baking powder. It was established tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…This explains the green color added to the flour samples by chia seeds and defatted chia seeds, which masked the yellow color while the two color blends reduced the brightness of a single color. A similar trend was observed by [37], where chia seeds reduced both the lightness and yellowness of wheat bread. It was noted that incorporation of DCF resulted in a significant difference in total color difference (∆E*) when compared to control at p < 0.05 at all levels of substitution.…”
Section: Colorsupporting
confidence: 82%
“…This explains the green color added to the flour samples by chia seeds and defatted chia seeds, which masked the yellow color while the two color blends reduced the brightness of a single color. A similar trend was observed by [37], where chia seeds reduced both the lightness and yellowness of wheat bread. It was noted that incorporation of DCF resulted in a significant difference in total color difference (∆E*) when compared to control at p < 0.05 at all levels of substitution.…”
Section: Colorsupporting
confidence: 82%
“…This purple wheat has been integrated seamlessly into the production of diverse finished products, such as cookies and pasta, offering consumers a delicious and healthenhancing alternative. 13,14 Previous investigations have primarily centered on exploring the influence of anthocyanins on the structural attributes of gluten proteins or their constituent parts. One study revealed that anthocyanins extracted from grape skins interact with gliadins, resulting in modifications to the protein's secondary structure.…”
Section: Introductionmentioning
confidence: 99%
“…Being a neurotoxic, Acrylamide may slow down nerve transmission, paralyze the hind limbs of rats, increase the landing foot spread, and cause the animals to drag their feet. In rat primary astrocytes, Acrylamide-induced apoptosis led to mitochondrial dysfunction (Bartkiene et al, 2023).…”
Section: Introductionmentioning
confidence: 99%